2017
DOI: 10.2147/amep.s139298
|View full text |Cite
|
Sign up to set email alerts
|

Should there be greater exposure to interventional radiology in the undergraduate curriculum?

Abstract: Medical imaging has been one of the most revolutionary innovations in medicine. Today, as health care professionals shift their focus toward more sophisticated technology and minimally invasive procedures, interventional radiology (IR) has become a rapidly expanding specialty. Despite these advances, there is a lack of doctors specializing in this field. A growing body of evidence suggests that the low number of applicants for posts may be due to poor exposure to the specialty at medical school. In this articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…In summary, we agree with Ojha et al 1 that the current role of IR in medicine warrants greater exposure to the field among medical students. With regard to implementing curricular change, we suggest a longitudinal clerkship model to enhance student understanding of IR.…”
Section: Dear Editorsupporting
confidence: 90%
See 1 more Smart Citation
“…In summary, we agree with Ojha et al 1 that the current role of IR in medicine warrants greater exposure to the field among medical students. With regard to implementing curricular change, we suggest a longitudinal clerkship model to enhance student understanding of IR.…”
Section: Dear Editorsupporting
confidence: 90%
“…We read with great interest the article by Ojha et al 1 in which the authors expressed concern over the lack of doctors choosing interventional radiology (IR) as a subspecialty and predicted a shortage of interventional radiologists in the future. The authors suggest that this shortage may be due to low exposure to IR in the medical curriculum and suggest possible solutions to this issue.…”
Section: Dear Editormentioning
confidence: 99%
“…However, due to only recent accreditation of IR as a sub-specialty, modules for IR based teaching have not been amalgamated into undergraduate medical curriculum. In several studies across different countries, medical students have demonstrated a poor understanding of IR, owing to suboptimal teaching and exposure levels (O'Malley and Athreya 2012; Atiiga et al 2017;de Gregorio et al 2018;Commander et al 2014;Leong et al 2009;Ghatan et al 2010;Nissim et al 2013;Foo et al 2018;Ojha et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to only recent accreditation of IR as a sub-specialty, modules for IR based teaching have not been amalgamated into undergraduate medical curriculum. In several studies across different countries, medical students have demonstrated a poor understanding of IR, owing to suboptimal teaching and exposure levels [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%